Edukasi Sanitasi Lingkungan Di Wilayah Pesisir Dalam Upaya Penurunan Angka Stunting - Hatapayo, Soleha; Cahyawati, Sunik; Lapodi, Abd Rijali; Tunny, Rahma (Fakultas Ilmu Kesehatan, 2025)
Stunting is a chronic nutritional problem in toddlers characterized by shorter height compared to children of the same age. One of the indirect causes is the availability of inadequate and unsafe sanitation. Objective: This study is to determine the effect of environmental sanitation education on maternal knowledge in efforts to reduce stunting rates in Telutih Baru Village, Tehoru District. Method: This study uses the Pre-Experiment method with a one group pre-test and post-test design. The population in this study were 45 mothers who had toddlers aged ≤ 2 years. While the sample in this study was 45 mothers who had toddlers aged ≤ 2 years in Teluti Baru Village, Tehoru District. The sampling technique used the total sampling technique. The research instrument used a questionnaire in the form of statements, the variables in this study were environmental sanitation education variables and maternal knowledge. The analysis used in this study was the Wilcoxon Test. Analysis of the Influence of Environmental Sanitation Education on Mother's Knowledge in Efforts to Reduce Stunting Rates in Teluti Baru Village, Tehoru District in 2024 from the results of the Wilcoxon Test, the significance value is 0.000 and this value is smaller than the alpha value of 0.005. There is a significant influence after respondents are given education or Ha is accepted, meaning that there is an influence of education using video media on mothers' knowledge of environmental sanitation in Teluti Baru Village, Tehoru District in 2024.